Study on the Production Factors in the Process of Production and Properties of Fly Ash-Based Coarse Aggregates - K. N. Shivaprasad; Bibhuti Bhusan Das (Advances in Civil Engineering)
An optimization study was carried out for the sustainable production of coarse aggregates from fly ash and alkaline solution, considering the combined effect of alkaline solution and production process. The trial mixes during the process of producing the artificial aggregates were designed through Taguchi’s experimental design method. The combined effect of alkaline solution (geopolymerisation) and production process (pelletization factors) along with engineering properties of the produced coarse aggregates was evaluated using response indices at different curing ages. Furthermore, the influence of each individual factor of geopolymerisation and pelletization on the engineering properties was determined through grey relational analysis to identify the most influencing factors in the production of coarse aggregates. The results obtained from grey relational analysis indicate that the properties of produced aggregates are governed mostly by geopolymerisation. It is also observed that water content of 20% by mass of fly ash is found to be essential for the suitable production of coarse aggregates and factors such as Na2O content and curing regime improved the engineering properties.